Daktilitas dan Beban Lentur Dinding Panel Semen Eceng Gondok (Emen Wall) - Prasetyo, Lukito (Jurnal Teknik Industri, 2009)
It is a follow-up research to discover water hyancinth wall panel building material characteristic (emen wall). Previous study found this material fulfilled the standard of PUBI 1982, SNI 03-6861.1-2002, and ASTM C423-90a in physically,Â  mechanically, acoustically, and burning endurance. Furthermore, the material will be evaluated through flexure test. Object test, which is a block board in 56X35X7 cm, will be burdened in interval of 100 kg until collapes. Then, deflection will be recorded based on the effective burden. ThisÂ  examination will emerge average devition ductility factors in amount of 15.04 and average flexure ductility in amount of 17.10. Refers to Park and Pauly (1975) water hyacinth wall panel (emen wall) collapsing type is ductile.